Recovery of FTO coated glass substrate via environment-friendly facile recycling perovskite solar cells. Issue 24 (19th April 2021) - Chowdhury, M. S.; Rahman, Kazi Sajedur; Selvanathan, Vidhya; Hasan, A. K. Mahmud; Jamal, M. S.; Samsudin, Nurul Asma; Akhtaruzzaman, Md.; Amin, Nowshad; Techato, Kuaanan
Abstract : Organic–inorganic perovskite solar cells (PSCs) have recently emerged as a potential candidate for large-scale and low-cost photovoltaic devices. Abstract : Organic–inorganic perovskite solar cells (PSCs) have recently emerged as a potential candidate for large-scale and low-cost photovoltaic devices. However, the technology is still susceptible to degradation issues and toxicity concerns due to the presence of lead (Pb). Therefore, investigation on ideal methods to deal with PSC wastes once the device attains its end-of-life is crucial and to recycle the components within the cell is the most cost effective and energy effective method by far. This paper reported on a layer-by-layer extraction approach to recycle the fluorine-doped tin oxide (FTO) coated glass substrate which is the most expensive component in the device architecture of mesoporous planar PSC. By adapting the sequential removal of each layer, chemical properties of individual components, including spiro-OMeTAD and gold can be preserved, enabling the material to be easily reused. It also ensured that the toxic Pb component could be isolated without contaminating other materials. The removal of all individual layers allows the retrieval of FTO conductive glass which can be used in various applications that are not only restricted to photovoltaics. Comparison of electrical, morphological and physical properties of recycled FTO glasses to commercial ones revealed minimal variations. This confirmed that the recycling approach was useful in retrieving the substrate without affecting its physicochemical properties.